Design of Hydraulic Folding Table to Minimize the Use of the Room - Julian Robecca; Handi Haryanto; Hendry Hardianto; Andy Ardiasandy; N P Dewi (Peneliti.net, 2021)
The purpose of this research is to make a table that does not require a large space so that it can be used at home or a place that does not have a large room. The method used in this study is the Ulrich method. It is used in this study to explain the steps in designing a product. The results obtained in this study are five available concepts. The concepts are evaluated and filtered carefully so that two concepts are chosen to be developed. It is done by comparing the ranking value and weight of each concept to make it easier to use formulas to assist in the assessment process. The chosen concept will be used to design the product. With the framework specifications using hollow iron, hydraulic drive, and magnetic holder, as well as bearing as a player and wood as a table mat. In conclusion, several phases must be passed in designing a product so that the results obtained will be satisfactory.